Autocrine Hepatocyte Growth Factor Provides a Local Mechanism for Promoting Axonal Growth - Yang, Xiu-Ming (J Neurosci, 1998)
In this report, we describe a novel local mechanism necessary for optimal axonal growth that involves hepatocyte growth factor (HGF). Sympathetic neurons of the superior cervical ganglion coexpress bioactive HGF and its receptor, the Met tyrosine kinase, both in vivo and in vitro. Exogenous HGF selectively promotes the growth but not survival of cultured sympathetic neurons; the magnitude of this growth effect is similar to that observed with exogenous NGF. Conversely, HGF antibodies that inhibit endogenous HGF decrease sympathetic neuron growth but have no effect on survival. This autocrine HGF is required locally by sympathetic axons for optimal growth, as demonstrated using compartmented cultures. Thus, autocrine HGF provides a local, intrinsic mechanism for promoting neuronal growth without affecting survival, a role that may be essential during developmental axogenesis or after neuronal injury.